CHARACTERISATION OF RECHARGE PROCESSES AND GROUNDWATER FLOW MECHANISMS IN WEATHERED-FRACTURED GRANITES OF HYDERABAD (INDIA) USING ISOTOPES - Sukhija B.S.; Reddy D.V.; Nagabhushanam P.; Bhattacharya S.K.; Jani R.A.; Kumar D. (My University, 2006)
In order to address the problem of realistic assessment of groundwater potential and its sustainability, it is vital to study the recharge processes and mechanism of groundwater flow in fractured hard rocks, where inhomogeneties and discontinuities have a dominant role to play. Wide variations in chloride, δ18O and 14C concentrations of the studied groundwaters observed in space and time could only reflect the heterogeneous hydrogeological setting in the fractured granites of Hyderabad (India). This paper, based on the observed isotopic and environmental chloride variations of the groundwater system, puts forth two broad types of groundwaters involving various recharge processes and flow mechanisms in the studied granitic hard rock aquifers. Relatively high 14C ages (1300 to ~6000 yr B.P.), δ18O content (−3.2 to −1.5‰) and chloride concentration (<100 mg/l) are the signatures that identified one broad set of groundwaters resulting from recharge through weathered zone and subsequent movement through extensive sheet joints. The second set of groundwaters possessed an age range Modern to ~1000 yr B.P., chloride in the range 100 to ~350 mg/l and δ18O from −3.2 to +1.7‰. The δ18O enrichment and chloride concentration, further helped in the segregation of the second set of groundwaters into three sub-sets characterized by different recharge processes and sources. Based on these processes and mechanisms, a conceptual hydrogeologic model has evolved suggesting that the fracture network is connected either to a distant recharge source or to a surface reservoir (evaporating water bodies) apart from overlying weathered zone, explaining various resultant groundwaters having varying 14C ages, chloride and δ18O concentrations. The surface reservoir contribution to groundwater is evaluated to be significant (40 to 70%) in one subset of groundwaters. The conceptual hydrogeologic model, thus evolved, can aid in understanding the mechanism of groundwater flow as well as migration of contaminants to deep groundwater in other fractured granitic areas.
Keywords: FRACTURED ROCKS; GROUNDWATER RECHARGE PROCESSES; GROUNDWATER FLOW MECHANISM; RADIOCARBON; STABLE ISOTOPES; CONCEPTUAL MODEL